Primary Economics Sustainability in the National Strategic Area of ​​Gerbangkertosusila - Alif Dewantara; Ahmad Herlyasa Sosro Pratama; Aminatur Romadhona; Rofiku Amin (Innovation Business Management and Accounting Journal, 2024)
Evaluation of sustainable development that has been carried out becomes the main discourse in this study, as a basis for further development planning and creating regional economic sustainability. This issue will be analyzed using the Regional Sustaibility Account (RSA) method to quantify the primary sector sustainability situation in Gerbangkertosusila which significantly affects the capacity to create sustainable development pathways and industrial policies that are more reflective in understanding the implications of sustainable development cycles. The limitation of this method is that the values and data presented come from partial sources per Regency/City. Thus, the results presented are in the form of partial economic sustainability status as well. The results of the analysis found that regencies/cities in the national strategic area of Gerbangkertosusia with a large industrial support base experienced disruptions to the continuity of the primary supply base which in turn could lead to unsustainability. In general, the results obtained are Gresik and Bangkalan districts with Chronic unsustainable criteria. Mojokerto and Sidoarjo Regencies on the Almost unsustainable criteria. Surabaya City on Sustainable criteria and Lamongan Regency on Good sustainable criteria.